2022
DOI: 10.1590/2179-10742022v21i3262417
|View full text |Cite
|
Sign up to set email alerts
|

MGF Methods for Fixed and Gain Saturated Optically Preamplified FSO Links Impaired by Misalignments and Atmospheric Turbulence

Abstract: The Gaussian approximation is commonly used to evaluate the performance of free space optical communication systems. However, other performance evaluation methods such as the saddle point approximation, Chernoff bound and the modified Chernoff bound have also been used. This paper investigates the performance of fixed and gain saturated optically preamplified communication systems limited by factors such as strong atmospheric turbulence and pointing errors using various evaluation methods. Average bit error ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…2(a), minimum average BER results for FSO communication systems using a non-adaptive decision threshold show that in gain saturated and fixed gain preamplified FSO communication systems using single or multiple transmitters, the best average BER performances were observed with 𝐷 π‘Ÿπ‘’π‘™ values of about 0. values of about 0.5. These results for FSO communication systems with increased number of transmitters align with earlier works [20], [30] with a single transmitter, where it was shown that to obtain optimal average BER performances, 𝐷 π‘Ÿπ‘’π‘™ should have values of about 0.2 and 0.5 when a non-adaptive decision threshold and an adaptive decision threshold is used at the receiver respectively. Note that based on these results, the 𝐷 π‘Ÿπ‘’π‘™ used for the adaptive and non-adaptive decision thresholds in Figs.…”
Section: Ber Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…2(a), minimum average BER results for FSO communication systems using a non-adaptive decision threshold show that in gain saturated and fixed gain preamplified FSO communication systems using single or multiple transmitters, the best average BER performances were observed with 𝐷 π‘Ÿπ‘’π‘™ values of about 0. values of about 0.5. These results for FSO communication systems with increased number of transmitters align with earlier works [20], [30] with a single transmitter, where it was shown that to obtain optimal average BER performances, 𝐷 π‘Ÿπ‘’π‘™ should have values of about 0.2 and 0.5 when a non-adaptive decision threshold and an adaptive decision threshold is used at the receiver respectively. Note that based on these results, the 𝐷 π‘Ÿπ‘’π‘™ used for the adaptive and non-adaptive decision thresholds in Figs.…”
Section: Ber Analysissupporting
confidence: 88%
“…The advantage of using a preamplifier was also shown in [3] as systems with a preamplifier performed better than systems without a preamplifier by about 6dB at the same target BER. In [20], the author used evaluation methods such as the gaussian approximation (GA), saddle point approximation (SPA) and modified Chernoff bound (MCB) to analyse the performance of FSO communication system consisting of a single receiver and a single transmitter. In [20], BER results were obtained while considering AT, GS, PE and ASE noise effects.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations